Angiolipoma of the stomach presenting with anaemia - Nam, Yang Hoon; Park, Sung Chul; Kim, Hee Jung; Lee, Sung Won; Kim, Jaihwan; Choi, Dae Hee; Kang, Chang Don; Lee, Sung Joon; Lee, Seungkoo (Gastroenterology Review/Przegląd Gastroenterologiczny, 2014)
Angiolipoma is a morphological variation of the lipoma and is a benign tumour that consists of mature adipose tissue and proliferating blood vessels. It occurs very rarely in the digestive tract, especially the stomach. We report a gastric angiolipoma in a 58-year-old woman admitted for anaemia and melena. Endoscopy showed a large polypoid mass with superficial ulceration in the anterior wall of the gastric antrum. Endoscopic ultrasound showed an about 2 cm sized isoechoic lesion at the third echo layer, with the echogenic portion on the luminal side of the lesion. Laparoscopic wedge resection was performed and histological examination showed that the lesion had encapsulated adipose tissue at the submucosal layer and stromal fibrosis just below superficial ulceration. There were blood vessels with thick walls among the mature fat cells. Therefore, the lesion was diagnosed as an angiolipoma.